Pathomorphological and immunohistochemical features of the esophageal mucosa in children with asthma combined with reflux esophagitis - T. D. Zadorozhna; Yu. H. Antypkin; T. R. Umanets; A. A. Buratynska; T. M. Archakova; M. I. Kiurdzhiieva; S. M. Kylykhevych (Zaporozhye State Medical University, 2021)
The most common comorbid pathology in children with asthma is gastroesophageal reflux disease (GERD) associated with reflux esophagitis (RE), which ranges from 32 % to 80 %. Histological changes of the esophageal mucosa in RE have been described in adults and children, but there are only isolated studies that describe the morphological features of the esophageal mucosa in combined pathology, taking into account the severity of asthma. The aim is to study the histological and immunohistochemical features of the esophageal mucosa in children with asthma combined with reflux esophagitis. Materials and methods. In 43 children aged 6-17 years with RE and severe asthma (group 1), with mild/moderate asthma (group 2) and without asthma (group 3), mucosal biopsies from the distal and proximal esophagus were examined by histological and immunohistochemical methods. Immunohistochemical research was performed in serial paraffin sections according to standard protocols using monoclonal antibodies to Ki-67, MMP-9, VEGF, BCL-2, IgE and CD68. Results. In children with asthma combined with RE, the structural changes of the esophageal mucosa differed depending on the severity of asthma. Severe basal epithelial hyperplasia was registered in 92.31 % of children in group 1, and its frequency was significantly different from children in groups 2 and 3. A characteristic feature of children with asthma and reflux esophagitis was dyschronosis, which was characterized by foci of hypo- and hypertrophy of basal layer cells (92.31 % of children in group 1 and 37.50 % of children in group 2). Severe elongation of the "papillae" was found only in 38.46 % of children in group 1. Immunohistochemical features of the esophageal mucosa of children with asthma and reflux esophagitis revealed the expression of Ki-67 antigen, IgE and a weak macrophage response (CD68), the severity of which differed from children with reflux esophagitis without asthma. Conclusions. Morphological changes in the esophageal mucosa of children with reflux esophagitis and asthma differ from children with reflux esophagitis without asthma in the presence of severe epithelial damage, dyschronosis of changes, severe elongation of the "papillae", pronounced cell proliferation (Ki-67) and local IgE expression.